Proposal of a new scoring formula for the Dermatology Life Quality Index in psoriasis. (19th September 2018) - Rencz, F.; Gulácsi, L.; Péntek, M.; Poór, A.K.; Sárdy, M.; Holló, P.; Szegedi, A.; Remenyik, É.; Brodszky, V.
Summary: Background: 'Not relevant' responses (NRRs) on the Dermatology Life Quality Index (DLQI) may occur in up to 40% of patients with psoriasis. As these responses are scored as the item of the questionnaire having no impact on the patients' lives at all, it is more difficult for these patients to fulfil the DLQI > 10 criterion required by clinical guidelines to become candidates for systemic treatment including biologics. Objectives: We propose a new scoring system for the DLQI that corrects for the bias in the NRR option and test its construct validity in a sample of patients with psoriasis. Methods: Data from 242 patients (104 of whom marked at least one NRR) from two earlier cross‐sectional surveys were reanalysed. For each patient, the DLQI score was calculated in two ways: (i) according to the original scoring and (ii) by applying a new scoring formula (DLQI‐R) that adjusts the total score for the number of NRRs. The construct validity of the DLQI‐R was tested against the Psoriasis Area and Severity Index (PASI) and EQ‐5D‐3L. Results: The mean DLQI and DLQI‐R scores were 9·99 ± 7·52 and 11·0 ± 8·02, respectively. The DLQI‐R allowed eight more patients (3·3%) to achieve the 'PASI > 10 and DLQI > 10' threshold. The results were robust when limiting the maximum number of NRRs allowed to two or three. Compared with the DLQI, DLQI‐R correlated slightly better with PASI ( r s = 0·59 vs. 0·57) and EQ‐5D‐3L index scores ( r s = −0·58 vs. −0·54). Conclusions: The DLQI‐R seems to be a valid scoring system for avoiding the bias in the NRR option and can help to improve patients' access to biologics. Abstract : What's already known about this topic? 'Not relevant' responses on the Dermatology Life Quality Index (DLQI) may occur in up to 40% of patients with psoriasis. As these responses are scored as the item having no impact on patients' lives at all, it is more difficult for these patients to fulfil the DLQI > 10 criterion required by guidelines to become candidates for systemic treatment including biologics. What does this study add? This study proposes a new scoring system for the DLQI that corrects for the bias in the 'not relevant' response option. We demonstrated the new scoring system's construct validity in a sample of patients with psoriasis. What are the clinical implications of this work? The new scoring can help to improve patients' access to biologics. Linked Editorial: Finlay and Sampogna. Br J Dermatol 2018; 179 :1021–1022. Respond to this article Plain language summary available online